The potency of alpha-humulene as HER-2 inhibitor by molecular docking - Putra, I Made Harimbawa; Pratama, I Putu Ari Anggara Catur; Putra, Komang Dian Aditya; Pradnyaswari, G. A. Desya; Laksmiani, Ni Putu Linda (Pharmacy Reports, 2022)
HER-2 overexpression is present in approximately 20% of breast cancer. This research aims to study the interactions of α-humulene to HER-2 protein by using in silico molecular docking. The experiment was carried out by HER-2 protein preparation (PDB ID 3PP0), docking validation, α-humulene optimization, and α-humulene docking. The results showed that α-humulene had binding energy of -7.50 kcal/mol, Van der Waals binding energy of -7.48 kcal/mol, and electrostatic energy of -0.02 kcal/mol. α-Humulene is potential as anti-breast cancer towards HER-2 in silico.